Association of caseins with β-lactoglobulin influenced by temperature and calcium ions: A multi-parameter analysis. (April 2023) - Mohammad-Beigi, Hossein; Wijaya, Wahyu; Madsen, Mikkel; Hayashi, Yuya; Li, Ruifen; Maria Rovers, Tijs Albert; Jæger, Tanja Christine; Buell, Alexander K.; Hougaard, Anni Bygvrå; Kirkensgaard, Jacob J.K.; Westh, Peter; Ipsen, Richard; et al.
Abstract: Aggregation of the major whey protein in bovine milk, β-lactoglobulin (β-Lg) is strongly influenced by association with caseins (CNs). Here, by using combined differential scanning fluorimetry and dynamic light scattering, the conformational stability and aggregation propensity of β-Lg and three types of CNs (α, β and ĸCNs) as well as their mixture have been systematically evaluated at different temperatures and Ca 2+ concentrations in a multi-parametric approach. While β-Lg was affected significantly through denaturation and resulting aggregation by heat treatment with little dependency on Ca 2+, αCN and βCN were influenced considerably by Ca 2+ . Through modifying the aggregation of β-Lg, CNs showed a different chaperone-like activity among the three types which were markedly dependent on the temperature and Ca 2+ concentration. The presence of CNs resulted in smaller mixed aggregates compared to pure β-Lg aggregates, mainly through interaction of CNs with unfolded β-Lg and also by influencing the process of β-Lg unfolding. This was further confirmed by small angle X-ray scattering and isothermal titration calorimetry indicating that Ca 2+ enhanced the interaction between β-Lg and CNs. Our experimental approach sheds light on molecular understanding of CN- β-Lg interactions and provides insight into how micro-structural assembly of milk proteins can be modulated to enable different functionalities in milk-based products. Graphical abstract: Image 1 Highlights: Ca 2+ and heating enhanced the aggregation of caseins and β-lactoglobulin. Caseins showed chaperone-like activity against β-lactoglobulin aggregation. Caseins reduced the aggregation of unfolded β-lactoglobulin in the absence of Ca 2+ . Caseins reduced the size of β-lactoglobulin aggregates in the presence of Ca 2+ . Caseins and unfolded β-lactoglobulin form stable aggregates.